2014
DOI: 10.1177/1049731514554854
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Parenting Stress Index–Short Form With Minority Caregivers

Abstract: Objectives There has been little examination of the structural validity of the Parenting Stress Index–Short Form (PSI-SF) for minority populations in clinical contexts in the Unites States. This study aimed to test prespecified factor structures (one-factor, two-factor, and three-factor models) of the PSI-SF. Methods This study used confirmatory factor analysis in a sample of 240 predominantly Black and Latino caregivers of children with behavioral difficulties. Results The three-factor model fit was reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 56 publications
5
39
0
Order By: Relevance
“…The first 33 items are rated on a five-point Likert scale from "Strongly Disagree" to "Strongly Agree", with three items also rated into one of five options. In the present study with 408 Iranian parents, a factor analysis of the 36 items broadly replicated the three subscales in the original standardization study in the USA, which other studies have confirmed (e.g., [16]). Total scores were then calculated for three subscale items: (1) Parental Distress (12 items); (2) Difficult Child (13 items); (3) Parent-Child Dysfunctional Interactions (11 items).…”
Section: Methodssupporting
confidence: 83%
“…The first 33 items are rated on a five-point Likert scale from "Strongly Disagree" to "Strongly Agree", with three items also rated into one of five options. In the present study with 408 Iranian parents, a factor analysis of the 36 items broadly replicated the three subscales in the original standardization study in the USA, which other studies have confirmed (e.g., [16]). Total scores were then calculated for three subscale items: (1) Parental Distress (12 items); (2) Difficult Child (13 items); (3) Parent-Child Dysfunctional Interactions (11 items).…”
Section: Methodssupporting
confidence: 83%
“…The findings suggested that parenting stress construct which consisted of 30 items could be used to measure the stress experienced by parents of children with autism spectrum disorder in Arab. Lee, et al (2016) conducted a study on minority population i.e. Afro and Latin caregivers of children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Parenting Stress Index has been translated and used in various countries, such as the United States of America (Lee, Gopalan, & Harrington, 2016), China (Tam, Chan, & Wong, 1994;Yeh, Chen, Li, & Chuang, 2001), Spain (Diaz-Herrero, Brito de la Nuez, López-Pina, Pérez-López, & Martínez-Fuentes, 2010;Solis & Abidin, 1991), and Korea (Lee, 2011). It has also been applied in numerous studies related to parenting stress in parents of children with ASD (Al-khalaf, Dempsey, & Dally, 2014;Boonen, Esch, Lambrechts, & Maljaars, 2015;Farrell, 2012;Foody, James, & Leader, 2015;Hoffman et al, 2008;Mahoney, 2009;May et al, 2015;Richardson, 2010;Rodger, Keen, Braithwaite, & Cook, 2008;Wang et al, 2013;Zablotsky, Bradshaw, & Stuart, 2013;Zaidman-Zait et al, 2017).…”
mentioning
confidence: 99%
“…The results of fit indices were mixed, which may suggest that the model did not fit the data well. However, wellknown and widely used measures often do not always report well-fitting of identified factors (e.g., the Parent Stress Index-Short Form) (Deater-Deckard & Scarr 1996;Haskett et al 2006;Lee et al 2016;Reitman et al 2002), and a model that is incorrectly specified still can fit well (Kline 2011). Another limitation in this study is that we tried to make children in three out-of-home care systems comparable using random selection of the study sample and random split of the collected data to conduct EFA and CFA.…”
Section: Discussionmentioning
confidence: 99%